Perbedaan Pengaruh Penambahan Pernapasan Diafragma Pada Latihan Konsep Bobath Terhadap Kemampuan Fungsional Pasien Stroke Di Rsud Dr. Tengku Mansyur Tanjungbalai - Ashri Pramudya Eka Putra; Trisno Susilo; Ronald Erwansyah (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Background: stroke is an occurred of functional focal brain more than two hours couse occoure of cerebral blood flow. Stroke can cause various kinds of disorders like a brain tissue death, loss of muscle tone, and loss of sensibility in some body parts which can reduce the ability of the body funtion controlled by these tissues. The bobath concept exercise is a personal exercise such as optimizing functionality with increase postural control and selective movement by facilitation of stroke patients. The diafragmatic breathing is one of those breathing exercise technique on focuses on the diafragm muscle which function as spinal stability exercise. In the end the exercise of bobath concept and the diaframatic breathing aims to improve the functional ability of stroke in carrying out daily activities, such as eating, shower, hygine, dressing, defecating, urinating, using the toilet, transfer, mobility, take the stairs.Objective: The purpose of this study was to find the different effect between combination of bobath voncept and diafragmatic breathing and bobath consept training to increase functional activity on case of stroke.Methods: The type of research is a quasi experiment research, two group pre test and post test design. Group A is given a Combination training of Bobath Concept and Diafragmatic Breathing group B is given a training of Bobath Concept toward patient of stroke. The measure of increasing of functional activity it use Indeks Barthel measurement, the assesment is obtained before and after therapy. This research is done at 1 July 2022 – 31 July 2022Results: The statistic test of effect to A group p<0,05 (p=0,000), B group p<0,05 (p=0,000), the two groups comparison is resulting effect differece of p>0,05 (p=0.632).Conclusion: The Combination of Bobath Concept Training and Diafragmatic Breathing given toward patient of stroke both can give improvement of functional activity.Keyword: Stroke, Bobath Concept Training, Diafragmatic Breathing